Inactivation of Nell-1 in chondrocytes significantly impedes appendicular skeletogenesis - Qi, Huichuan (J Bone Miner Res, 2018)
NELL-1, an osteoinductive protein, has been shown to regulate skeletal ossification. Interestingly, an interstitial 11p14.1-p15.3 deletion involving the Nell-1 gene was recently reported in a patient with short stature and delayed fontanelle closure. Here we sought to define the role of Nell-1 in endochondral ossification by investigating Nell-1-specific inactivation in Col2α1 expressing cell lineages. Nell-1(flox/flox); Col2α1-Cre(+) (Nell-1(Col2α1)KO) mice were generated for comprehensive analysis. Nell-1(Col2α1)KO mice were born alive but displayed subtle femoral length shortening. At 1 and 3 months postpartum, Nell-1 inactivation resulted in dwarfism and premature osteoporotic phenotypes. Specifically, Nell-1(Col2α1)KO femurs and tibias exhibited significantly reduced length, BMD, BV/TV, trabecular number/thickness, cortical volume/thickness/density, and increased trabecular separation. The decreased bone formation rate revealed by dynamic histomorphometry was associated with altered numbers and/or function of osteoblasts and osteoclasts. Furthermore, longitudinal observations by in vivo micro-CT showed delayed and reduced mineralization at secondary ossification centers in mutants. Histologically, reduced staining intensities of Safranin O, Col-2, Col-10, and fewer BrdU-positive chondrocytes were observed in thinner Nell-1(Col2α1)KO epiphyseal plates along with altered distribution and weaker expression level of Ihh, Patched-1, PTHrP, and PTHrP receptor. Primary Nell-1(Col2α1)KO chondrocytes also exhibited decreased proliferation and differentiation, and its downregulated expression of the Ihh-PTHrP signaling molecules can be partially rescued by exogenous Nell-1 protein. Moreover, intra-nuclear Gli-1 protein and gene expression of the Gli-1 downstream target genes, Hip-1 and N-Myc, were also significantly decreased with Nell-1 inactivation. Notably, the rescue effects were diminished/reduced with application of Ihh signaling inhibitors, cyclopamine or GANT61. Taken together, these findings suggest that Nell-1 is a pivotal modulator of epiphyseal homeostasis and endochondral ossification. The cumulative chondrocyte-specific Nell-1 inactivation significantly impedes appendicular skeletogenesis resulting in dwarfism and premature osteoporosis through inhibiting Ihh signaling and predominantly altering the Ihh-PTHrP feedback loop.